Acute Basilar Artery Occlusion: Outcome of Mechanical Thrombectomy with Solitaire Stent within 8 Hours of Stroke Onset - Baek, J.M.; Yoon, W.; Kim, S.K.; Jung, M.Y.; Park, M.S.; Kim, J.T.; Kang, H.K. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Mechanical thrombectomy with a stent retriever applied shortly after symptom onset could increase good functional outcomes and improve survival in patients with acute basilar artery occlusion, but this has not yet been studied. This study evaluated the efficacy and safety of mechanical thrombectomy with a Solitaire stent within 8 hours of stroke onset in patients with acute basilar artery occlusion. MATERIALS AND METHODS: We analyzed 25 consecutive patients with acute basilar artery occlusion who were treated with mechanical thrombectomy by use of the Solitaire stent within 8 hours of stroke symptom onset. Successful recanalization was defined as TICI grade 2b or 3. Good outcome was defined as mRS score of 0–2 at 3 months. Clinical and radiologic data in patients with good outcomes were compared with those with poor outcomes. RESULTS: Successful recanalization was achieved in 96% (24/25) of patients, and 48% (12/25) of patients had good outcomes. Eighty-eight percent (22/25) of patients survived to 3 months. The median NIHSS score on admission was significantly lower in patients with good outcomes than in those with poor outcomes (9.5 versus 14, P = .005). Procedure-related complications occurred in 2 patients (8%). No symptomatic intracerebral hemorrhages occurred. CONCLUSIONS: The current study suggests that mechanical thrombectomy by use of a Solitaire stent within 8 hours of stroke onset increases good outcomes and improves survival in patients with acute basilar artery occlusion. BAObasilar artery occlusionIAintra-arterialBASICSBasilar Artery International Cooperation Study